If Precipitation Extremes Are Increasing, Why Aren't Floods?. Issue 11 (16th November 2018) - Sharma, Ashish; Wasko, Conrad; Lettenmaier, Dennis P.
Abstract: Despite evidence of increasing precipitation extremes, corresponding evidence for increases in flooding remains elusive. If anything, flood magnitudes are decreasing despite widespread claims by the climate community that if precipitation extremes increase, floods must also. In this commentary we suggest reasons why increases in extreme rainfall are not resulting in corresponding increases in flooding. Among the possible mechanisms responsible, we identify decreases in antecedent soil moisture, decreasing storm extent, and decreases in snowmelt. We argue that understanding the link between changes in precipitation and changes in flooding is a grand challenge for the hydrologic community and is deserving of increased attention. Plain Language Summary: It is now well established that rising temperatures are increasing precipitation extremes. This has led many to believe that flood magnitude and hence risk are also increasing, while observational evidence suggests otherwise. This commentary outlines the reasons for this dichotomy and presents mechanisms that may be contributing to it. The implications of increasing precipitation extremes leading to reducing flood magnitudes are discussed, and an argument is made that understanding this changing link between the two is deserving of increased attention. Key Points: Extreme precipitation is increasing with rising temperatures Flood magnitudes, however, are decreasing at the same time However, this is not a complete story; very rare floods are rising while frequent floods are reducing; reasons for this are explored